A survey of severe acute respiratory coronavirus virus 2 (SARS-CoV-2)-positive healthcare providers: Household prevention measures and stress early in the pandemic - Sebastian Otero; Leena B. Mithal; Anum I. Khan; Antonia S. Willnow; Ami B. Patel; Mehreen Arshad (Cambridge University Press, 2021)
Measures to prevent coronavirus disease 2019 (COVID-19) spread to household members was assessed by surveying COVID-19-positive physicians and advanced practice providers. Showering and changing were more common than physical distancing. Half of respondents reported a symptomatic household member. Most reported increased stress, worsening of mental health, and concerns about illness and impact on family.